1980
DOI: 10.1080/10408398009527295
|View full text |Cite
|
Sign up to set email alerts
|

Cereal sprouts: Composition, nutritive value, food applications

Abstract: The practice of sprouting of cereal grains has become popular in the western world. Sprouted grains are thought of as having exceptional nutritive value. Sprouting is easy and can be done without sophisticated equipment. Untreated seeds of good quality and high germination percentage are placed in an environment of adequate water, a desirable temperature, and a certain composition of gases in the atmosphere for several days for sprouting. The sprouts can be kept for a few days to over a week under refrigeratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 27 publications
10
82
1
1
Order By: Relevance
“…The crude protein and oil content of triticale were found 14.64% and 1.08% respectively. In case of protein content, the result found was greater while the oil content was lowered than the report by Grewal and Jood [5] but in agreement with Lorenz [6] report. The total carbohydrate content of triticale was resulted as 71.15% while the total ash content was 1.97%.…”
Section: Proximate Compositionsupporting
confidence: 47%
“…The crude protein and oil content of triticale were found 14.64% and 1.08% respectively. In case of protein content, the result found was greater while the oil content was lowered than the report by Grewal and Jood [5] but in agreement with Lorenz [6] report. The total carbohydrate content of triticale was resulted as 71.15% while the total ash content was 1.97%.…”
Section: Proximate Compositionsupporting
confidence: 47%
“…These processes are known to activate phytases, which in turn hydrolyze phytate, rendering iron and zinc more available. During germination, endogenous phytase activity in cereals and legumes increases as a result of de novo synthesis and/or activation, resulting in reductions in inositol penta-and hexa-phosphates depending on the species and variety (Lorenz, 1980;Bartnick and Szafranska, 1987;Chavan and Kadam, 1989;Reddy et al, 1989). Reddy et al (1989) have reported reductions in phytate ranging from 36% for sprouted soya beans to 53% for germinated lentils.…”
Section: Discussionmentioning
confidence: 99%
“…From two to three days on, the enzyme abilities of endopeptidases and carboxypeptidases increase rapidly, storage protein hydrolysis increases correspondingly, and the major products formed are amino acids and peptides. In addition, Lorenz (1980) reported that the sprouting of grains can cause a series of property changes including an increase in enzyme activity and total protein; changes in amino acid composition; a loss of total dry matter; a decrease in starch and sugars; a slight increase in crude fat and crude ®ber etc.…”
Section: Change In Molecular Weight Distribution Of the Soluble Protementioning
confidence: 99%